2020
DOI: 10.1177/0023830920930042
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Perceptual Epenthesis is Modulated by Transitional Probability

Abstract: Perceptual epenthesis is the perception of illusory vowels in consonantal sequences that violate native phonotactics. The consensus has been that each language has a single, predictable candidate for perceptual epenthesis, that vowel which is most minimal (i.e., shortest and/or quietest). However, recent studies have shown that alternate epenthetic vowels can be perceived when the perceptual epenthesis of the minimal vowel would violate native co-occurrence restrictions. We propose a potential explanation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…When another vowel has lower surprisal in a given context (e.g., [i] after palatal consonants), the vowel with the lower surprisal is epenthesized instead, suggesting that phonotactic information can override the use of a phonetically minimal segment. Kilpatrick et al ( 2020 ) also found similar results with [ɡ, ʧ, ʃ], where [u] was epenthesized more often after [ɡ] but [i] was epenthesized after the palatalized consonants [ʧ, ʃ].…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…When another vowel has lower surprisal in a given context (e.g., [i] after palatal consonants), the vowel with the lower surprisal is epenthesized instead, suggesting that phonotactic information can override the use of a phonetically minimal segment. Kilpatrick et al ( 2020 ) also found similar results with [ɡ, ʧ, ʃ], where [u] was epenthesized more often after [ɡ] but [i] was epenthesized after the palatalized consonants [ʧ, ʃ].…”
Section: Introductionmentioning
confidence: 61%
“…The epenthetic vowel after [p, k, g], [t], and [d] are predicted to be [a, o, e], respectively. In the case of [p, k, g], previous studies have shown repeatedly that it is in fact [u] that is epenthesized after these consonants (Dupoux et al, 1999(Dupoux et al, , 2011Whang, 2019;Kilpatrick et al, 2020). The results also show that neither [u] nor [i] In fact, high vowels are prohibited in the native and Sino-Japanese lexical strata of Japanese, and it is most often [o] that is epenthesized after coronal stops in loanwords (e.g., /faIt/ → [Faito] "fight"; Ito and Mester, 1995).…”
Section: Sublexical Surprisal Resultsmentioning
confidence: 99%
See 3 more Smart Citations